A importância das mídias e tecnologias no processo de ensino e aprendizagem de matemática - NASCIMENTO, Sancler Silva (2017)
The present study aims to analyze concepts, problems and contributions of the technologies inserted in education, focusing mainly on the use of media and technologies as tools of teaching Mathematics for high school students. As a highlight, the subject ”Information Society”is highlighted, seeking to emphasize historical and cultural issues related to technology and society. A description of a field research carried out with 10 teachers who work with the Mathematics in High School discipline and 02 managers of the Cleobeto de Oliveira Mesquita Teaching Center, the only middle school in the municipality of Santa Luzia do Paru´a, is also described. Within this description, the role, the formation and the educative practice of the educator in this new era is discussed, raising questions and reflections from the data related to exploratory-descriptive research.